2019
DOI: 10.1093/toxsci/kfz167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorpyrifos on Cholinesterase and Serine Lipase Activities and Lipid Metabolism in Brains of Rainbow Trout (Oncorhynchus mykiss)

Abstract: Chlorpyrifos is an organophosphorus insecticide that elicits acute toxicity through inhibition of acetylcholinesterase (AChE), leading to acetylcholine accumulation and prolonged stimulation of cholinergic receptors throughout the central and peripheral nervous systems. Previous studies have indicated that neurodevelopment may also be impaired through alternative pathways, including reduction of cyclic adenosine monophosphate (cAMP)-catalyzed downstream events. The upstream initiating events that underlie nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 71 publications
(82 reference statements)
2
5
0
Order By: Relevance
“…Decreased levels of several lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE) metabolites were found in steelhead exposed to the higher concentration of bifenthrin and were predicted to alter inflammatory response pathways (Figure B). Decreased concentrations of LPE (16:0) were previously reported in the brains of rainbow trout treated with 1.38 μg/L chlorpyrifos, with significant differences at nearly every carbon length. The top canonical pathway in the brains of Atlantic salmon dietarily exposed to 8 mg/kg chlorpyrifos-methyl was inflammation .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Decreased levels of several lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE) metabolites were found in steelhead exposed to the higher concentration of bifenthrin and were predicted to alter inflammatory response pathways (Figure B). Decreased concentrations of LPE (16:0) were previously reported in the brains of rainbow trout treated with 1.38 μg/L chlorpyrifos, with significant differences at nearly every carbon length. The top canonical pathway in the brains of Atlantic salmon dietarily exposed to 8 mg/kg chlorpyrifos-methyl was inflammation .…”
Section: Discussionsupporting
confidence: 52%
“…DHA makes up 40% of the polyunsaturated fatty acids (PUFAs) in the brain where it is highly concentrated in neuronal membranes . Chlorpyrifos, an organophosphorus pesticide that is a potent irreversible inhibitor of acetylcholinesterase activity in nerve cells, was reported to decrease DHA levels in the brains of exposed rainbow trout and was associated with olfactory impairment . DHA, also acting as the primary ligand for the activation of the retinoid X receptor (RXR), was a top canonical pathway predicted to be affected in chlorpyrifos-methyl-exposed Atlantic salmon (Salmo salar). Increased RXR receptor activation may alter lipid metabolism and inflammatory responses .…”
Section: Discussionmentioning
confidence: 99%
“…Similar reductions of TGs were observed in the brains of rainbow trout treated with 1.38 μg/L chlorpyrifos. 39 Atlantic salmon hepatocytes exposed to a mixture of chlorpyrifos-methyl, pirimiphos-methyl, and nonylphenol at a concentration of 100 μM also had a significantly reduced abundance of TGs. 40 There was an upregulation in lipase ( lipe ) mRNA expression reported in chlorpyrifos-exposed hepatocytes, which has a prominent role in the hydrolysis of TGs.…”
Section: Discussionmentioning
confidence: 95%
“… 62 Chlorpyrifos treatments (1.38 μg/L) in rainbow trout for 7 days did not have significantly altered levels of PC in brain tissue, with only a slight decrease in PE levels being reported. 39 An imbalance between levels of PE and PC in the brain is the major driver of motor neuron survival, which has implications for the incidence of neuronal disease 60 and may be a contributing factor to bifenthrin-induced neurotoxicity, as previous studies have reported that other fishes residing within the Delta, such as inland silversides ( Menidia beryllina ) and Delta smelt ( Hypomesus transpacificus ), exposed to bifenthrin have induced neurobehavioral effects, which could potentially have population-level consequences. 63 65 Alterations in PC and PE levels may be related to increased levels of fatty acids that are stored as TGs in lipid droplets within the cell, comprising a monolayer of phospholipids, 40 and known to be present in higher numbers in vacuole membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) inhibition is the main mechanism of action of organophosphates [ 71 , 72 , 73 ]. The enzyme is essential and necessary for hydrolysis of the neurotransmitter acetylcholine (ACh), and plays a fundamental role in controlling synaptic transmission in all animals; hydrolyzing acetylcholine to end its synaptic action [ 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%